(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Husain DA, Aziz ZS. 2021. Short Communication: Molecular study of bacteria isolated from meat and chicken frozen from Misan Governorate market in Iraq. Biodiversitas 23: 81-86. Food contamination is frequently defined as spoiled or tainted foods because they contain microorganisms, such as fungi, bacteria, parasites, or toxic substances that make them unfit for consumption. In this study, one hundred meat and chicken Frozen products samples were collected randomly from the commercial markets in Misan Governorate, Iraq from November 2020 to April 2021, included: (burger – sausage – kebab – shawarma – minced meat) of meat and (chest-thigh-liver-burger-kebab) of Chicken. The results of aerobic plate count showed that all meat and chicken products were contaminated with bacteria, but the imported products were more contaminated than the local products. Our study included the isolation and diagnosis of eighteen bacterial species by using routine and standard bacteriological tests. The results showed that Gram-negative bacteria were common in meat products (52%) and Gram-positive bacteria represented 48%. In chicken samples, the Gram-positive bacteria was most dominant (59%) while the percentage of Gram-negative bacteria was 41%. Monoplex PCR was used to identify eighteen bacterial strains using a universal 16S rRNA primer that gave 1500 bp amplification product, nucleotide sequences were studied at the National Center for Biotechnology Information (NCBI) using the Basic Local Alignment Search Tool (Nucleotide BLAST). The diagnosed bacteria were Aeromonas veronii, Pseudomonas plecoglossicida, Acinetobacter lwofii, Aeromonas veronii, Klebsiella pneumoniae, Pseudomonas japonica, Pseudomonas songnenensis, Klebsiella pneumoniae subsp. ozaenae, Psychrobacter sanguinis, Klebsiella pneumoniae strain, Acinetobacter lwofii, Lysinibacillus boronitolerans, Bacillus licheniformis, Enterobacter hormaechei, Pseudomonas putida strain, Serratia liquefaciens strain, Comamonas testosterone strain, and Methylogaea oryzae strain which recorded in the Gene Bank belong to different accession numbers.